Amblyomma mixtum Koch, 1844 (Acari: Ixodidae): First record confirmation in Colombia using morphological and molecular analyses - Rivera-Páez, Fredy A. [UNESP]; Labruna, Marcelo B.; Martins, Thiago F.; Sampieri, Bruno Rodrigues [UNESP]; Camargo-Mathias, Maria I. [UNESP] (Elsevier, 2016)
Up to some years ago, the taxon Amblyomma cajennense represented a single tick species in the New World, from southern United States to northern Argentina. Recent studies, based on genetic, reproductive and morphological data reorganized this taxon into a complex of the following 6 valid species: A. cajennense sensu stricto, Amblyomma mixtum, Amblyomma sculptum, Amblyomma interandinum, Amblyomma tonelliae, and Amblyomma patinoi. According to this classification, the A. cajennense complex is currently represented in Colombia by only one species, A. patinoi. Because the Colombian land is surrounded by confirmed records of A. mixtum in Panama and Ecuador, and by A. cajennense s.s. in Venezuela and the Brazilian Amazon, it is possible that these two species could also occur in Colombia. This study aimed to determine the occurrence of ticks of the A. cajennense complex in the Orinoquía region of Colombia. A total of 246 adult ticks of the Amblyomma genus were collected in three sampled regions: 71 females and 110 males in Arauca (Arauca Department), 27 females and 20 males in Nunchía (Casanare Department), and 10 females and 8 males in Yopal (Casanare Department). Based on morphological and molecular analyses, these ticks were identified as A. mixtum. Molecular analyses consisted of DNA sequences of two molecular markers, the nuclear second internal transcribed spacer (ITS2) and the mitochondrial cytochrome c oxidase subunit I gene (COI). The presence of A. mixtum in Colombia is of medical relevance, since this species is incriminated as a vector of Rickettsia rickettsii in Central America.
Keywords: Amblyomma cajennense; Complex; Molecular markers; Rickettsia rickettsii